Scout Culture and its Relationship with Scout Curricula According to the Perspective of the Sustainable Development Goals among Scout Leaders in Iraq - Magda Abbas Muhammad Ali; Mahmood Dawood Salman; Amna Fadel Mahmoud (Institute of Medico-legal Publications Pvt Ltd, 2021)
The Scout movement is considered a tool for upbringing and building for generations in a way thatreflects positively on the civilized, scientific and social development of society, for it is no longer justa means to occupy the leisure time of youth, but rather has become a contribution to developing theirabilities and behaviour by developing their social skills, instilling sound values and ethics for them, andenriching their knowledge with movements and information that It can contribute to providing themwith experiences that qualify them physically, mentally and socially as individuals who are good citizensin their societies to build a generation capable of serving their homeland. Values have a great and directinfluence on the work that the mobile performs in terms of controlling his behavior and defining hisgoals And taking decisions related to its work, and the extent of the relationship of scouting curriculaaccording to the perspective of the sustainable development goals with the application of scout culturein the behavior of scouts, the research objectives. the research community was identified with leadersand scout leaders in the education directorates in the governorates of Iraq except for the Kurdistanregion for the academic year 2019-2020, and the researchers identified the research sample in a randomway, Whereas, (10) leaders and female leaders were selected for the reconnaissance experiment, (40)leaders and female leaders for the construction sample.